Generation and Characterization of Live Attenuated Influenza A(H7N9) Candidate Vaccine Virus Based on Russian Donor of Attenuation - Shcherbik, Svetlana (PLoS One, 2015)
BACKGROUND: Avian influenza A (H7N9) virus has emerged recently and continues to cause severe disease with a high mortality rate in humans prompting the development of candidate vaccine viruses. Live attenuated influenza vaccines (LAIV) are 6:2 reassortant viruses containing the HA and NA gene segments from wild type influenza viruses to induce protective immune responses and the six internal genes from Master Donor Viruses (MDV) to provide temperature sensitive, cold-adapted and attenuated phenotypes. METHODOLOGY/PRINCIPAL FINDINGS: LAIV candidate A/Anhui/1/2013(H7N9)-CDC-LV7A (abbreviated as CDC-LV7A), based on the Russian MDV, A/Leningrad/134/17/57 (H2N2), was generated by classical reassortment in eggs and retained MDV temperature-sensitive and cold-adapted phenotypes. CDC-LV7A had two amino acid substitutions N123D and N149D (H7 numbering) in HA and one substitution T10I in NA. To evaluate the role of these mutations on the replication capacity of the reassortants in eggs, the recombinant viruses A(H7N9)RG-LV1 and A(H7N9)RG-LV2 were generated by reverse genetics. These changes did not alter virus antigenicity as ferret antiserum to CDC-LV7A vaccine candidate inhibited hemagglutination by homologous A(H7N9) virus efficiently. Safety studies in ferrets confirmed that CDC-LV7A was attenuated compared to wild-type A/Anhui/1/2013. In addition, the genetic stability of this vaccine candidate was examined in eggs and ferrets by monitoring sequence changes acquired during virus replication in the two host models. No changes in the viral genome were detected after five passages in eggs. However, after ten passages additional mutations were detected in the HA gene. The vaccine candidate was shown to be stable in the ferret model; post-vaccination sequence data analysis showed no changes in viruses collected in nasal washes present at day 5 or day 7. CONCLUSIONS/SIGNIFICANCE: Our data indicate that the A/Anhui/1/2013(H7N9)-CDC-LV7A reassortant virus is a safe and genetically stable candidate vaccine virus that is now available for distribution by WHO to vaccine manufacturers.